Flow of Goods Across Customs Territories - Cedilnik, Marko (Naše gospodarstvo/Our economy, 2013)
Purpose – The purpose of this paper is to explore systemic relationships within sup- ply chains, which are created as a result of passing goods between customs territories. Specifically, this research focuses on how business entities can reduce the time consumed for the execution of mandatory customs controls at border crossings by applying the voluntary implementation of certain legally standardized institutes—in this case, the status of authorized economic operator (AEO). Design/methodology/approach – The study hypotheses were tested at two levels. The fundamental hypothesis was tested using a survey of participants’ subjective perceptions. To verify the supporting hypothesis, the survey was carried out using numerical techniques (i.e., an analysis of the queuing systems). Findings – The research results show that acquisition of an AEO certificate can facil- itate the acceleration of the flow of goods across customs territories. To achieve the optimum reduction of time delays caused by interruptions in the flow of goods resulting from controls conducted by authorities, it would be necessary to adapt the road infrastructure at the border crossings.